2018
DOI: 10.1155/2018/2930519
|View full text |Cite
|
Sign up to set email alerts
|

Transpalpebral Electrical Stimulation as a Novel Therapeutic Approach to Decrease Intraocular Pressure for Open-Angle Glaucoma: A Pilot Study

Abstract: Purpose To determine the effect on intraocular pressure of transpalpebral specific exogenous voltages in a cohort of open-angle glaucoma patients. Methods This is a prospective, comparative, and experimental pilot study. The electrical stimuli applied consisted of 10 Hz, biphasic, nonrectangular current pulses (100 μA) delivered from an isolated constant current stimulator. At intake, baseline IOP measurements were obtained from each eye. The measurement was repeated before and after microstimulation until the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…Pre-chiasmatic rtACS Age-related macular degeneration Gall et al,2010;Fedorov et al, 2011;Gall et al, 2011;Schmidt et al, 2013;Bola et al, 2014;Gall et al, 2016;Shinoda et al, 2008;Anastassiou et al, 2013;Chaikin et al, 2015;Gil-Carrasco et al, 2018;Fujikado et al, 2006;Inomata et al, 2007;Oono et al, 2011;Schatz et al, 2011;Naycheva et al, 2013;Ozeki et al, 2013;Robles-Camarillo et al, 2013;Schatz et al, 2017;Bittner et al, 2018;Bittner et al, 2018;Ota et al, Campana et al, 2014;Camilleri et al, 2016;Moret et al, 2018;Halko et al, 2011;Plow et al, 2011;Plow et al, 2012a;Plow et al, 2012b;Cowey et al, 2013;Olma et al, 2013;Ding et al, 2016;Kim et al, 2016;Alber et al, 2017;Matteo et al, 2017 tDCS Post-stroke visual perception degradation Amblyopia Myopia Notes: rtACS: repetitive transorbital alternating current stimulation, tpES: transpalpebral electrical stimulation, tcES: transcorneal electrical stimulation, hf-tRNS: high-frequency random noise stimulation, tDCS: transcranial direct current stimulation. studies used this technique to treat retinitis pigmentosa.…”
Section: Site Of Stimulation Kind Of Clinical Conditions First Authormentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-chiasmatic rtACS Age-related macular degeneration Gall et al,2010;Fedorov et al, 2011;Gall et al, 2011;Schmidt et al, 2013;Bola et al, 2014;Gall et al, 2016;Shinoda et al, 2008;Anastassiou et al, 2013;Chaikin et al, 2015;Gil-Carrasco et al, 2018;Fujikado et al, 2006;Inomata et al, 2007;Oono et al, 2011;Schatz et al, 2011;Naycheva et al, 2013;Ozeki et al, 2013;Robles-Camarillo et al, 2013;Schatz et al, 2017;Bittner et al, 2018;Bittner et al, 2018;Ota et al, Campana et al, 2014;Camilleri et al, 2016;Moret et al, 2018;Halko et al, 2011;Plow et al, 2011;Plow et al, 2012a;Plow et al, 2012b;Cowey et al, 2013;Olma et al, 2013;Ding et al, 2016;Kim et al, 2016;Alber et al, 2017;Matteo et al, 2017 tDCS Post-stroke visual perception degradation Amblyopia Myopia Notes: rtACS: repetitive transorbital alternating current stimulation, tpES: transpalpebral electrical stimulation, tcES: transcorneal electrical stimulation, hf-tRNS: high-frequency random noise stimulation, tDCS: transcranial direct current stimulation. studies used this technique to treat retinitis pigmentosa.…”
Section: Site Of Stimulation Kind Of Clinical Conditions First Authormentioning
confidence: 99%
“…TpES is shown to act via the same mechanisms as tcES, with an additional effect on intraocular pressure via BKCa 2 channel modulation. For this reason, it has also been suggested for glaucoma treatment (Gil-Carrasco et al, 2018). In three articles, tpES was used to treat AMD.…”
Section: Site Of Stimulation Kind Of Clinical Conditions First Authormentioning
confidence: 99%
“…Another important early detection instrument is electroretinography (ERG), that allows to objectively quantify the retinal function by detecting retinal electrical responses. In addition, electrical stimulation has been performed as a novel approach to decrease IOP in open-angle glaucoma (Gil-Carrasco et al, 2018). Preclinical studies on gerbil eyes demonstrated that early transcorneal electrical stimulation (TcES) has a positive effect on RGC survival after retinal injury related to acute ocular-hypertension, protecting these cells from damage through modulation of the inflammatory response activated by microglial cells (Fu et al, 2018).…”
Section: Glaucoma Screeningmentioning
confidence: 99%
“…Preclinical studies on gerbil eyes demonstrated that early transcorneal electrical stimulation (TcES) has a positive effect on RGC survival after retinal injury related to acute ocular-hypertension, protecting these cells from damage through modulation of the inflammatory response activated by microglial cells (Fu et al, 2018). Transpalpebral electrical stimulation (TES) performed on human eyes (Gil-Carrasco et al, 2018) has been proven to significantly lower IOP in eyes with open-angle glaucoma. The aim of TES is to reproduce the role of tyrosine kinase inhibitors, stimulating the reactivation of Ca 2+ channels in the TM cells and so promoting their relaxation in order to promote the outflow of aqueous humor to the Schlemm's channel.…”
Section: Glaucoma Screeningmentioning
confidence: 99%
“…In general, positive effects were found on the development, functionality, and stability of retinal nerve cells ( Sehic et al, 2016 ). Human studies mainly investigated the effect of ocular current stimulation on neurodegenerative eye diseases such as glaucoma ( Röck et al, 2014 ; Gil-Carrasco et al, 2018 ; Ota et al, 2018 ), retinitis pigmentosa ( Schatz et al, 2011 , 2017 ; Wagner et al, 2017 ; Jolly et al, 2020 ), Stargardt disease ( Röck et al, 2013 ), macular degeneration ( Shinoda et al, 2008 ; Anastassiou et al, 2013 ; Chaikin et al, 2015 ), retinal artery occlusions ( Inomata et al, 2007 ; Naycheva et al, 2013 ), or optic neuropathy ( Fedorov et al, 2011 ; Gall et al, 2011 ; Sabel et al, 2011 ). The relationship between stimulation parameters such as current intensity, frequency, or duration and the current effects on the retinal cells remained ambiguous ( Sehic et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%